Child Maltreatment and Quality of Life Among Urban Chinese Children - Sun, Xiaoyue (Journal of interpersonal violence, 2021)
Child maltreatment is an international public health problem. The aftermath can appear in multiple aspects of individual health and development, including decreased physical and emotional function, posttraumatic stress disorder (PTSD), and suicide attempts. However, there is lack of evidence regarding the quality of life of maltreated children. This study aims to examine the association between children’s maltreatment experience and their quality of life. This study employed a cross-sectional design and surveyed 1,093 primary school children (including migrant children and nonmigrant children) in Shanghai, China. The Parent–Child Conflict Tactics Scale (CTSPC) and Pediatrics Quality of Life Inventory were used to measure children’s experiences of child maltreatment and their quality of life. Corporal punishment (89.47%) was the most prevalent form of child maltreatment, followed by physical assault (80.21%), psychological abuse (65.00%), and neglect (52.26%). Children’s migration status was not associated with their quality of life; however, social capital factors were all associated with increased levels of quality of life. Children’s victimization experience, including severe to very severe physical assault (β = −3.34/−3.80, p < .001), psychological assault (β = −3.74, p < .001), corporal punishment (β = −2.46, p < .01), and neglect (β = −4.31, p < .001), was associated with their decreased quality of life. The results show that child maltreatment threatens the quality of life of children. There is a need for developing effective interventions to prevent child maltreatment and reduce the adverse outcomes among children with maltreatment experiences.